2004
DOI: 10.1111/j.1600-6143.2004.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Humoral Rejection of Human Lung Allografts and Elevation of C4d in Bronchoalveolar Lavage Fluid

Abstract: Antibody-mediated rejection is well established for renal allografts but remains controversial for lung allografts. Cardinal features of antibody-mediated rejection in renal allografts include antibodies to donor human leukocyte antigen (HLA) and evidence for antibody action, such as complement activation demonstrated by C4d deposition. We report a lung allograft recipient with circulating antibodies to donor HLA who failed treatment for acute cellular rejection but responded to therapy for humoral rejection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] In 2002, Magro and colleagues 30 introduced the term ''septal capillary injury syndrome'' to describe alterations in the alveolar spaces and interstitium, usually alveolar septal necrosis, observed in patients with decline in pulmonary function. Complement (C1q, C3, C4d and/or C5b-9) and immunoglobulin deposition of variable intensity were seen in the majority of biopsies.…”
Section: Current Status Of Pathologic Diagnosis Of Amrmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] In 2002, Magro and colleagues 30 introduced the term ''septal capillary injury syndrome'' to describe alterations in the alveolar spaces and interstitium, usually alveolar septal necrosis, observed in patients with decline in pulmonary function. Complement (C1q, C3, C4d and/or C5b-9) and immunoglobulin deposition of variable intensity were seen in the majority of biopsies.…”
Section: Current Status Of Pathologic Diagnosis Of Amrmentioning
confidence: 99%
“…8 When positive, tissue histopathology for C4d may constitute an important confirmatory signal. 6,12,18,19 In this single-center retrospective study, we identified additional risks of DSAs and AMR, including a CF diagnosis, HLA class II DSAs with anti-DQ specificity, BOS, and possibly, ACR.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, subsequent surveillance biopsies lacked C4d positivity, suggesting pathologic resolution of his prior antibody-mediated rejection, which has not been documented previously in cases suggestive of antibody-mediated rejection. 14 The absence of cellular rejection on the second biopsy (POD 33) without any intervening treatment was somewhat unexpected. It is possible that this was due to sampling error, but the biopsies included 6 pieces of alveolated parenchyma that were sufficient for the diagnosis of antibody-mediated rejection.…”
Section: Discussionmentioning
confidence: 95%